A Novel Targeted Nanoliposomal Atorvastatin Transdermal Patch Assisted with Solid Microneedles for Improved Bioavailability - Srikakulam, Sai Ramya; Devineni, Jyothirmayee; Mokkapati, Chandana; Venigalla, Yaswanth; Pothuri, Aparna; Acchi, Anuhya; Sharma, Sushil (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives The present study investigated the alternate route of delivery to avoid first pass metabolism and to increase bioavailability by nanosized Liposomes (LP) with Microneedles (MNs) Assistance for the Delivery of Atorvastatin (AVT), a HMG CoA reductase inhibitor in which the role of commercial Epyz derma Roller (poke and patch) MN arrays containing 540 Titanium Microneedles (MNs) with dissimilar micro-needle lengths (0.25, 0.5, 1.5, 2.5 mm) in improving the in vitro permeation of AVT-LP over pig ear skin was evaluated. Materials and Methods AVT-LP were formulated and optimized using four methods and evaluated for microscopy, % drug entrapment efficiency, drug-excipient compatibility studies, In vitro drug release studies, In vitro skin permeation studies. Formulation F4 prepared by thin film hydration method with egg lecithin: cholesterol ratio 1:2, found to be having 92.219±0.965 drug entrapment efficiency and 92.53±0.621 drug release within 24 hr with significant physical and chemical stability. The optimized AVT-LP formulation F4 was prepared into a transdermal patch and using Franz diffusion cells, in vitro skin permeation studies were evaluated for a period of 24 hr. Results and Discussion The optimized AVT-LP, were <100 nm in diameter and showed an ordered state of good lamellarity. From the dermatokinetic study it was noticeable that the delivery of MN assisted AVT into the excised porcine skin was significantly higher (p <0.05) with cumulative % drug permeation of 90.13±0.231 for 2.5 mm MNs than that from AVT-LP patch without the help of MNs. Conclusion Nanosized MN assisted AVT-LP could avoid oral route first pass metabolism and increase bioavailability.
Keywords: Liposomes; Atorvastatin; Microneedles; Transdermal drug delivery systems; Bioavailability; Anti hyperlipedemic